Developing The Educational Game Tool to Improve Reading Ability of Early Childhood - Khadijah, Khadijah; Pulungan, Enny Nazrah; Hariati, Rizki; Maisarah, Maisarah (Universitas Negeri Makassar, 2022)
This research aims to developing the educational game tool (word tree) to improve reading ability of early childhood. This is research used Borg & Gall model and has been modified with six steps, they are potential and problem, data collection, product design, design validation, resign revision, and usage trial. The subject is 5-6 years old children in RA Babul Ilmi Rantauparapat. The instrument used is validation questionnaire sheet. Data analysis technique is formulation of mean score percentage and gain score. The research result showed that: (1) the development of educational game too (word tree) is very worthy to be used to improve reading children of 5-6 years old children; and (2) educational game tool (word tree) developed has high level of effectiveness in improving reading ability of 5-6 years old children. This research suggest to the readers, teachers and other researchers to be creative and innovative in designing learning activity, which one of them is developing the product giving real contribution for their students’ ability. This research developed educational game tool in form of word tree that did not only improve children’s reading ability but also create happiness to learn.